Septin Assembly and Remodeling at the Cell Division Site During the Cell Cycle - Marquardt, Joseph; Chen, Xi; Bi, Erfei (Frontiers in Cell and Developmental Biology, 2021)
The septin family of proteins can assemble into filaments that further organize into different higher order structures to perform a variety of different functions in different cell types and organisms. In the budding yeast Saccharomyces cerevisiae, the septins localize to the presumptive bud site as a cortical ring prior to bud emergence, expand into an hourglass at the bud neck (cell division site) during bud growth, and finally “split” into a double ring sandwiching the cell division machinery during cytokinesis. While much work has been done to understand the functions and molecular makeups of these structures, the mechanisms underlying the transitions from one structure to another have largely remained elusive. Recent studies involving advanced imaging and in vitro reconstitution have begun to reveal the vast complexity involved in the regulation of these structural transitions, which defines the focus of discussion in this mini-review.